Clinical Impact of Re-irradiation with Carbon-ion Radiotherapy for Lymph Node Recurrence of Gynecological Cancers - Shiba, Shintaro; Okonogi, Noriyuki; Kato, Shingo; Wakatsuki, Masaru; Kobayashi, Daijiro; Kiyohara, Hiroki; Ohno, Tatsuya; Karasawa, Kumiko; Nakano, Takashi; Kamada, Tadashi (Anticancer research, 2017)
To evaluate the safety and efficacy of re-irradiation with carbon-ion radiotherapy (C-ion RT) for lymph node recurrence of gynecological cancers after definitive radiotherapy. Data regarding patients with unresectable and isolated recurrent lymph node from gynecological cancer after definitive radiotherapy were analyzed. Total dose of C-ion RT was 48-57.6 Gy (RBE) in 12 or 16 fractions. Sixteen patients received re-irradiation by C-ion RT were analyzed. Median follow-up was 37 months. Median tumor size was 27 mm. None developed Grade 1 or higher acute toxicities and Grade 3 or higher late toxicities. The 3-year overall survival, local control and disease-free survival rates after C-ion RT were 74%, 94% and 55%, respectively. Re-irradiation with C-ion RT for lymph node recurrence of gynecological cancers after definitive radiotherapy can be safe and effective. This result suggested that C-ion RT could be a curative treatment option for conventionally difficult-to-cure patients.